Removal of Triclosan, Ibuprofen, Amoxicillin and Paracetamol Using Organic Residues Under a Bibliometric-Statistical Analysis - Villamar-Ayala, C; Madariaga-Segovia, P (Elsevier Ltd, 2023)
Triclosan, ibuprofen, amoxicillin, and paracetamol have increased their use due to the COVID-19 pandemic. However, organic residues emerge as a viable treatment alternative to remove them. This study evaluated the use of organic residues for removing these emerging contaminants through bibliometric and statistical analyses. Methodology was based on bibliometric analysis (keywords co-occurrence) using 114 scientific publications (2010−2022). ANOVA two-ways and multiple correlation analysis were applied. Co-occurrence analysis showed the main keywords: “adsorption”, “activated carbon”. Systematic analysis showed an increase of up to 25.4 % scientific publications/year in the last decade, where ibuprofen removal was the most studied (38.6 %). The highest adsorption capacity (p > 0.05) of organic residues was given by herbaceous and agricultural biomass (HAB), with mean values of 90 (triclosan), 48.2 (amoxicillin), and 152 (paracetamol) mg/g. Paracetamol obtained the lowest mean removal (72.3 %) and amoxicillin the highest (87.8 %). The main variable influencing their removal was the surface area (p < 0.05, r2 = 0.52–0.77). © 2023 Elsevier Ltd